2018
DOI: 10.3390/ijerph15050841
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Vaccination in Health Care Workers. A Pre-Post Intervention Study in an Italian Paediatric Hospital

Abstract: Despite relevant recommendations and evidences on the efficacy of influenza vaccination in health care workers (HCWs), vaccination coverage rates in Europe and Italy currently do not exceed 25%. Aim of the study is to measure the variations in vaccination coverage rates in an Italian pediatric hospital after a promotion campaign performed in the period October–December 2017. The design is a pre-post intervention study. The intervention is based on a wide communication campaign and an expanded offer of easy vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 44 publications
4
37
0
2
Order By: Relevance
“…However, the vaccination coverage registered in our teaching hospital represents an encouraging starting point and it is analogous, or even higher, than flu vaccination coverage rates registered in other national and regional settings [29,32,33,39,50,[53][54][55]. Our results confirmed that physicians are the professionals most willing to get vaccinated, as reported in the literature [20,33,50,54], even though the overall increase was the lowest during the considered period if compared to nurses and OHCWs. The job category that registered the highest increase in coverage rate (compared to the previous years) were the OHCWs (+76.3%) and the nurses (+75.8%), proving that the implemented strategies were effective in reaching groups originally less inclined to vaccination, maybe due to the wrong perception of being at low risk of illness or transmitting the infection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the vaccination coverage registered in our teaching hospital represents an encouraging starting point and it is analogous, or even higher, than flu vaccination coverage rates registered in other national and regional settings [29,32,33,39,50,[53][54][55]. Our results confirmed that physicians are the professionals most willing to get vaccinated, as reported in the literature [20,33,50,54], even though the overall increase was the lowest during the considered period if compared to nurses and OHCWs. The job category that registered the highest increase in coverage rate (compared to the previous years) were the OHCWs (+76.3%) and the nurses (+75.8%), proving that the implemented strategies were effective in reaching groups originally less inclined to vaccination, maybe due to the wrong perception of being at low risk of illness or transmitting the infection.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the overall vaccination coverage rate was lower than those reached in other international settings [22,27,29,51,52], thus remaining unsatisfactory and still far away by the minimum goal of 75% defined by the WHO and by the Italian PNPV (PNPV 2017-2019) [10,11]. However, the vaccination coverage registered in our teaching hospital represents an encouraging starting point and it is analogous, or even higher, than flu vaccination coverage rates registered in other national and regional settings [29,32,33,39,50,[53][54][55]. Our results confirmed that physicians are the professionals most willing to get vaccinated, as reported in the literature [20,33,50,54], even though the overall increase was the lowest during the considered period if compared to nurses and OHCWs.…”
Section: Discussionmentioning
confidence: 78%
“…The highest coverage rates were found in pediatric workers (data not shown) but the differences between these and other clinical groups were not statistically significant. Although international literature data on vaccination coverage among pediatricians are limited, higher coverage rates and more positive attitudes towards vaccinations have been reported [ 7 , 12 , 36 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to the fact that the accident insurance covers long-term effects on workers’ health. However, this should not discourage any attempts to improve coverage of HW vaccinations [39]. It is well proven that influenza vaccinations in HWs reduces working time lost [40].…”
Section: Discussionmentioning
confidence: 99%